Materialistic Cues Boosts Personal Relative Deprivation - Zhang, Hong; Zhang, Wen (Frontiers in Psychology, 2016)
Three studies investigated whether exposure to materialistic cues would increase perceptions of personal relative deprivation and related emotional reactions. In Study 1, individuals who were surveyed in front of a luxury store reported higher levels of personal relative deprivation than those surveyed in front of an ordinary building. In Study 2, participants who viewed pictures of luxurious goods experienced greater personal relative deprivation than those viewed pictures of neutral scenes. Study 3 replicated the results from Study 2, with a larger sample size and a more refined assessment of relative deprivation. Implications of these findings for future studies on relative deprivation and materialism are discussed.